1987
DOI: 10.1099/00222615-23-1-61
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia and seeding of capsulate Bacteroides spp. and anaerobic cocci

Abstract: Summary. The effect of capsulation on the ability of Bacteroides fragilis, B. asaccharolyticus and anaerobic gram-positive cocci to induce bacteraemia and seeding to various organs was investigated. The test species were injected into mice subcutaneously alone, or mixed with other aerobic or facultative organisms. Capsulate anaerobes were isolated more frequently from the blood, spleen, liver, and kidneys of infected animals than were non-capsulate organisms. After injection of single anaerobic strains, capsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
10
2
Order By: Relevance
“…The demonstration of synergy with facultative and anaerobic bacteria during the growth of abscesses, capsule formation and the ability to form hydrogen sulphide from glutathione have been described as important virulence factors (Brook & Walker, 1985;Brook, 1987Brook, , 1988aCarlsson et al, 1993). The demonstration of synergy with facultative and anaerobic bacteria during the growth of abscesses, capsule formation and the ability to form hydrogen sulphide from glutathione have been described as important virulence factors (Brook & Walker, 1985;Brook, 1987Brook, , 1988aCarlsson et al, 1993).…”
Section: Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration of synergy with facultative and anaerobic bacteria during the growth of abscesses, capsule formation and the ability to form hydrogen sulphide from glutathione have been described as important virulence factors (Brook & Walker, 1985;Brook, 1987Brook, , 1988aCarlsson et al, 1993). The demonstration of synergy with facultative and anaerobic bacteria during the growth of abscesses, capsule formation and the ability to form hydrogen sulphide from glutathione have been described as important virulence factors (Brook & Walker, 1985;Brook, 1987Brook, , 1988aCarlsson et al, 1993).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Parvimonas micra is one of the best studied of the GPAC in terms of characterisation of its virulence factors. The demonstration of synergy with facultative and anaerobic bacteria during the growth of abscesses, capsule formation and the ability to form hydrogen sulphide from glutathione have been described as important virulence factors (Brook & Walker, 1985;Brook, 1987Brook, , 1988aCarlsson et al, 1993). Furthermore, it has been described to adhere to gingival epithelial cells (Dzink et al, 1989) and to express immunoglobulin Fc-binding proteins (Grenier & Michaud, 1994).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…In 1958, Mergenhagen et al (178) reported synergy between "anaerobic streptococci" and S. aureus in causing progressive gangrene in rabbits; neither component was effective on its own, but cells of S. aureus could be replaced by a dialyzable cell filtrate of S. aureus. This work was extended in the 1980s by Brook and coworkers (18,19,25,47,48), who used a subcutaneous abscess model in the mouse. They demonstrated synergy of GPAC with facultative and anaerobic bacteria, including S. aureus, P. aeruginosa, several species of streptococci and members of the Enterobacteriaceae, in their ability to induce abscesses, enhance the growth of bacterial components, and increase mortality (19,25).…”
Section: Pathogenesis and Virulence Factorsmentioning
confidence: 99%
“…This work was extended in the 1980s by Brook and coworkers (18,19,25,47,48), who used a subcutaneous abscess model in the mouse. They demonstrated synergy of GPAC with facultative and anaerobic bacteria, including S. aureus, P. aeruginosa, several species of streptococci and members of the Enterobacteriaceae, in their ability to induce abscesses, enhance the growth of bacterial components, and increase mortality (19,25). These studies examined recent clinical isolates of P. anaerobius, P. asaccharolyticus, P. magnus, P. micros, and P. prevotii; they did not demonstrate clear differences between species of GPAC, but small numbers of strains were examined.…”
Section: Pathogenesis and Virulence Factorsmentioning
confidence: 99%
“…intermedia (6), Pr. oralis (5) and F. nucleaturn (6). All isolates were lyophilised within three subcultures of primary isolation.…”
Section: Bacteriamentioning
confidence: 99%